A high efficiency technique for the long-term preservation of infective nematode larvae. - Hubert, J (1997)
Improvements are suggested for the existing long term techniques for the preservation of nematode larvae. Haemonchus contortus, Teladorsagia circumcincta, Trichostrongylus colubriformis and Cooperia curticei larvae exsheathed in sodium hypochlorite and then suspended in phosphate buffered saline (PBS pH 7.2) are cooled in the gas over liquid nitrogen at a cooling rate of -1 degree C min-1 down to -50 degrees C. Larvae are then stored in liquid nitrogen at -196 degrees C. After warming at 30 degrees C and reactivation at 20 degrees C for at least 12 h, their percent motility is maintained (approximately 85%) providing that no more than 3000 to 5000 larvae are suspended in 1.8 mL of PBS in cryotubes. Infectivity does not significantly decrease: 46% of larvae cooled for 2 or 6 mo develop to adult stages compared to 52% for larvae stored at 4 degrees C for 2 mo.